Kualitas Kefir dengan Penambahan Tepung Daun Stevia (Stevia rebaudiana Bertoni) Sebagai Pemanis Alami - Dwi Rumdaini Intan Permatasari; Purwadi Purwadi; Herly Evanuarini (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2018)
Stevia is one of natural sweetener a substitute for sugar low calorie. Stevia start widely used as many consumers want sweetening healthy. Stevia leaf powder was used to develop an kefir as sweetener replacer to sugar. The objective of this research was to determine the best percentage of using stevia leaf flour as substitution ingredient on kefir based on total sugar, acidity, total solids and sineresis kefir. The materials research were fresh milk, kefir grain, and stevia leaf flour. The research method was using experimental design with four treatments and four replications. The treatments were P1 0.5 % stevia leaf flour, P2 0.75% stevia leaf flour P3Â  1% stevia leaf flour and P4 1.25% stevia leaf flour. The data were analyzed by ANOVA and if there were significant effect then would be continued by Duncanâ€™s Multiple Range Test (DMRT). The result showed that substituting sugar using stevia leaf flour gave highly significant different effect (P<0.01) on total sugar, acidity, total solids and sineresis kefir. It can be concluded that the kefir with the used 1.25% stevia leaf flour gave the best result with the total sugar was 6.82 , acidity was 0.55%, total solids was 11.75%, and sineresis was 23.75%.